Stem cell labeling with iron oxide nanoparticles: impact of 3D culture on cell labeling maintenance. (August 2016) - Kilian, Teresa; Fidler, Florian; Kasten, Annika; Nietzer, Sarah; Landgraf, Veronika; Weiß, Katrin; Walles, Heike; Westphal, Fritz; Hackenberg, Stephan; Grüttner, Cordula; Steinke, Maria
Aim: We aimed to analyze the suitability of nanoparticles (M4E) for safe human mesenchymal stem cell (hMSC) labeling and determined cell labeling maintenance in 2D and 3D culture.Materials & methods: We investigated cell–particle interaction and the particles' impact on cell viability, growth and proliferation. We analyzed cell labeling maintenance in 2D and 3D culture invasively and noninvasively.Results: M4E do not affect cell viability, growth and proliferation and do not cause chromosomal aberrations. Cell labeling maintenance is up to five-times higher in 3D conditions compared with 2D culture.Conclusion: M4E allow safe hMSC labeling and noninvasive identification. Our hMSC-loaded, 3D tissue-engineered construct could serve as a graft for regenerative therapies, in which M4E-labeled hMSCs can migrate to their target.